Biodegradable and recycle husk mailer from Cocos Nucifera / Anas Firdaus Zakaria ... [et al.] - Zakaria, Anas Firdaus; Hamzah, Nur Atirah; Abdull Patah, Siti Farahin; Wan Mohd Zain, Wan Zuraida; Hamid, Nur’ Amira (2021)
Coconut, the fruit of the coconut palm (Cocos nucifera) is a tree of the palm family of Arecaceae. Coconuts probably originated somewhere in Indo-Malaya and are one of the most important crops of the tropics (Ahuja et al., 2014). Besides the edible kernels and the drink obtained from green nuts, the harvested coconut also yields the dried extracted kernel, or meat, from which coconut oil, major vegetable oil is expressed. The dry husk yields coir or husk, a fibre highly resistant to saltwater and used in the manufacture of ropes, mats, baskets, brushes, and brooms. Through this coconut, our group is going to produce sustainable and environmental-friendly types of mailers which are made of coconut husk or coir named “Husk Mailer”. Husk Mailer is a very simple product to be produced. Mailer has been using since decades ago and there are few or zero sustainable mailers that have been produced. Mailers have two types which are padded and bubble wrap, the padded mailers can easily be recycled while for the bubble wrap mailers cannot be recycled as it is made of plastic. Our group creates the paper of the mailer from the recycled paper and mix them with the coconut husk. We choose them because we want to avoid wasting any of the waste from the coconut, that is when the idea of coconut husk mailer is generated. Through this biodegradable and recycle Husk Mailer, we are highly wanting to reduce plastic uses to sustain and keep our environment great again.